Assessing the knowledge of endometriosis diagnostic tools in a large, international lay population: an online survey. (1st September 2021) - Leonardi, M; Rocha, R; Tun‐Ismail, AN; Robledo, KP; Armour, M; Condous, G
Abstract : Objective: To assess the general population's knowledge regarding the utility and availability of tools to diagnosis endometriosis, with a focus on ultrasound. Design: An international cross‐sectional online survey study was performed between August and October 2019. Setting and population: 5301 respondents, representing 73 countries. Methods: In all, 23 questions survey focused on knowledge of endometriosis diagnosis distributed globally via patient‐ and community‐endometriosis groups using social media. Main outcomes and measures: Descriptive data of the knowledge of diagnostic tools for diagnosing endometriosis, including details about diagnosis using ultrasound. Results: In all, 84.0% of respondents had been previously diagnosed with endometriosis, 71.5% of whom had been diagnosed at the time of surgery. Ultrasound and MRI were the methods of diagnosis in 6.5% and 1.8%, respectively. A total of 91.8%, 28.8% and 16.6% of respondents believed surgery, ultrasound and MRI could diagnose endometriosis, respectively (more than one answer allowed). In those diagnosed by surgery, 21.7% knew about ultrasound as a diagnosis method, whereas in those diagnosed non‐surgically, 51.5% knew ( P < 0.001). In all, 14.7%, 31.1% and 18.2% stated superficial, ovarian and deep endometriosis could be diagnosed with ultrasound (32.9% stated they did not know which phenotypes of endometriosis could be diagnosed). Lastly, 58.4% of respondents do not believe they could access an advanced ultrasound in their region. Conclusions: There is a limited appreciation for the role of non‐surgical diagnostic tests for endometriosis among lay respondents to this survey. Tweetable abstract: International survey shows limited awareness of lay respondents about non‐surgical endometriosis diagnostic tools. Tweetable abstract: International survey shows limited awareness of lay respondents about non‐surgical endometriosis diagnostic tools.